Age and estimated glomerular filtration rate in Chinese older adults: a cohort study from 2014 to 2020 - Jiang, Ying; Cao, Qin; Hong, Weiqi; Xu, Tianwei; Tang, Molian; Li, Yun; Xu, Renying (Frontiers in Public Health, 2024)
This study aimed to fill the data gap of the course of renal function decline in old age and explore changes in renal function across different health states with increasing age. This observational, retrospective, single-center cohort study included 5,112 Chinese older adults (3,321 men and 1,791 women, range 60-104 years). The individual rate of estimated glomerular filtration rate (eGFR) decline was analyzed using linear mixedeffects model to account for repeated measures over the years. The median age was 66 years, median BMI was 24.56 kg/m2, and median eGFR was 89.86 ml/min.1.73 m2. For every 1-year increase in age, women's eGFR decreased by 1.06 ml/min/1.73 m2 and men's by 0.91 ml/min/1.73 m2. We observed greater age-related eGFR decline in men and women with high systolic blood pressure (SBP). Men with high triglyceride (TG), high low-density lipoprotein cholesterol (LDL-C), and low high-density lipoprotein cholesterol (HDL-C), had greater age-related eGFR decline. In women, different BMI groups showed significant differences in age-related eGFR decline, with the highest decline in those with obesity. Additionally, participants with normal baseline eGFR had a faster age-related decline than those with low baseline eGFR. The eGFR declined linearly with age in Chinese older adults, with women exhibiting a slightly faster decline than men. Both men and women should be cautious of SBP. Older adults with normal baseline renal function experienced a faster eGFR decline. Men with high TG, LDL-C, and low HDL-C levels, as well as obese women, should be vigilant in monitoring renal function.